A "turn-off" fluorescent sensor based on electrospun polycaprolactone nanofibers and fluorene(bisthiophene) derivative for nitroaromatic explosive detection. (December 2021) - Santos, Anna Paula L.A.; Deokaran, Gerard O.; Costa, Cristiane V.; Gama, Lillia I.L.M.; Mazzini Júnior, Edu G.; de Assis, Alexandro M.L.; de Freitas, Johnnatan D.; de Araujo, William R.; Dias, Roberta P.; da Silva, Júlio C.S.; Costa, Ligia M.M.; Ribeiro, Adriana S.
Abstract: The preparation of fluorene(bisthiophene)-based fluorescent nanofibers for nitroaromatic explosive detection provides a convenient rapid and low-cost strategy aiming at forensic applications. Polycaprolactone (PCL) and fluorene(bisthiophene) derivative (FBT) nanofibers were obtained by electrospinning technique as a free-standing mat and characterized by SEM, FTIR, thermal analysis and fluorescence spectroscopy. The PCL/FBT nanofibers presented high sensitivity towards 2, 4, 6-trinitrotoluene (TNT) and picric acid (PA), with fluorescence quenching ( turn-off mechanism), and selectivity to another kind of explosives. The free-standing mats were used as a cloth strip that was swiped on surfaces contaminated with TNT traces allowing its visual detection under UV light source. These findings are particularly important for the development of a facile and promising strategy to assembly portable optical devices for nitroaromatic explosive detection. Graphical Abstract: ga1 Highlights: Polymer nanofibers based on poly(caprolactone) and fluorene(bisthiophene) derivative have been successfully prepared. Fluorescent nanofiber mats are useful as material for nitroaromatic explosives detection. The strategy consists in fluorescence quenching of PCL/FBT mats after exposure to nitroaromatic explosive residues. Low-cost and free-standing fluorescent nanofibers formation are some of the advantages of the methodology. PCL/FBT nanofibers presented high efficiency quenching after interaction with TNT and PA.